RIVASTIGMINE TRANSDERMAL PATCH FOR ALZHEIMER’S DISEASE: A SYSTEMATIC REVIEW - Baskoro, Firza Yoga; Hassa, Nazwan; Hajar, Nabil; Balqis, Indira Aura (PERDOSNI (Perhimpunan Dokter Spesialis Neurologi Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Alzheimer's disease (AD) is the most common type of dementia disease. Acetylcholinesterase inhibitors (AChE-I) plays a pivotal role by increasing acetylcholine levels in the brain to improve cognitive function of Alzheimer's patients. Several agents including cholinesterase inhibitors such as donepezil and galantamine, as well as the NMDA receptor antagonist memantine are known for its benefit in increasing acetylcoline . However, Rivastigmin is the only AChE-I agent available in patch preparation. Objective : This study aims to evaluate the efficacy of Rivastigmin patch in improving cognitive function using the Alzheimer's Disease Assessment Scale Cognitive Subscale (ADAS-Cog) in Alzheimer's disease patients. Methods: This research was conducted in accordance with the Systematic Review without Meta-Analysis (SWiM) guideline. A systematic database search was conducted in Medline, Google Scholar, and Cochrane Central Libraries using a pre-determined search query. Articles were screened by independent reviewers for eligibility to be included in the study. After risk of bias was conducted, seven studies were included for this research. Results: The included studies reported varied outcomes regarding cognitive improvement in Alzheimer's disease (AD) patients, depending on the dosage of Rivastigmine used. Overall, Rivastigmine was found to slow the progression of cognitive decline, as measured by the ADAS-Cog, and in some cases, even reduced ADAS-Cog scores by up to 3 points . Rivastigmine patch is known to inhibit the action of acetylcholinesterase enzyme which causes degradation of acetylcholine in the synapse gap, ultimately improving the cognitive of AD patients. Studies also mention that Rivasitgmine patch preparation has better tolerance to side effects compared to capsules or placebo. Conclusion: Rivastigmine patch shows improvement of cognitive status in Alzheimer's patients and has good tolerability compared to placebo or capsule preparations. the long-term efficacy and safety of the rivastigmine patch remain underexplored, and the generalizability of the findings to diverse patient populations is uncertain.